Examining the Factor Structure of an Adapted Posttraumatic Growth Inventory in a Sample of Childhood Cancer Survivors: A Brief Report. Issue 1 (March 2023) - Stal, Julia; Ramirez, Cynthia N.; Huh, Jimi; Tobin, Jessica; Kim, Yoonji; Miller, Kimberly A.; Milam, Joel E.
Posttraumatic growth (PTG) represents positive changes following a trauma, crisis, and/or psychologically distressing event. Experiencing cancer can serve as a traumatic event for patients, resulting in life changes among survivors. Various PTG measures have been used to assess post-cancer change among childhood cancer survivors (CCS), but few have been evaluated for use in this population. This study examined the factor structure of an adapted, 11-item version of the Posttraumatic Growth Inventory (PTGI) among CCS. A randomly selected subgroup of participants ( N = 332) was selected from the Los Angeles Cancer Surveillance Program (mean age of 26.5 years at time of survey, mean age at diagnosis of 12 years, primarily male [53.6%], and Hispanic [51.5%]). Participants indicated the degree to which they experienced positive, negative, or no change in their life because of their cancer experience. An exploratory factor analysis (EFA) identified two factors: Appreciation of New Possibilities and Spiritual Change. The adapted, 11-item PTGI was deemed appropriate for use among CCS. Additional research is needed to confirm the use of the two-factor model with confirmatory factor analysis in an independent sample. Future research on PTG among CCS can consider spiritual change as a potential independent factor.